In silico analysis of cDNA libraries SH2 and SH3 for the identification of genes responsive to drought in coffee - Vinecky, Felipe; Silva, Felipe Rodrigues da; Andrade, Alan Carvalho (Coffee Science - ISSN 1984-3909, 2012)
Brazil is the largest producer and exporter of coffee and coffee production is a major source of income for small farmers. Drought, which has become increasingly intense over the years, affects the production of these farmers, as it reduces productivity and can even cause entire crop loss. Aiming at the development of drought tolerant crops, several research groups are currently studying the genetic factors involved in plant responses to drought. The construction and sequencing of EST libraries (Expressed Sequence Tags) is a quick and effective way to obtain information about most expressed genes. The functional genome of coffee made available by cDNA sequencing (ESTs), allowed the construction of a large EST database of three different Coffea species . The Coffee EST Database provides a rich source of information for genetic and physiological studies of coffee plants. The goal of this study was to identify genes potentially involved in the response of coffee plants to water stress by means of an (in silico) analysis of available ESTs of the coffee genome database. The methodology was based on in silico comparisons between EST data from libraries SH2 (Coffea arabica) and SH3 (Coffea canephora), with the aid of bioinformatics tools available at the Coffee Genome Database. With the methodology used, several candidate genes have been identified and may be subject to further experimental studies aiming at the establishment of a breeding program based on marker assisted selection for quick development of drought tolerant varieties of coffee.